Desiring the Bomb : Communication, Psychoanalysis, and the Atomic Age - Matheson, Calum L., 1981- (Book collections on Project MUSE., 2019)
"A timely interdisciplinary study that applies psychoanalysis and the rhetorical tradition of the sublime to examine the cultural aftermath of the Atomic Age"--